ALDOSTERONE INDUCES CYP11B2 GENE EXPRESSION VIA GPER-1 ACTIVATION IN HUMAN ADRENOCORTICAL CELL (HAC15) AND STRIPS FROM ALDOSTERONE PRODUCING ADENOMA. (June 2018) - Caroccia, B.; Seccia, T.M.; Piazza, M.; Delfino, F.; Rossi, G.P.
Abstract: Objective: We previously reported that GPER-1 is mostly expressed in the zona glomerulosa of normal human adrenal gland and in aldosterone-producing adenoma (APA). In the adrenocortical carcinoma cell line HAC15 17b-estradiol induces aldosterone synthesis via GPER-1 activation. Since GPER-1 was found to bind not only 17b-estradiol, but also aldosterone in endothelial and vascular smooth muscle cells, we wondered if aldosterone binds GPER-1 receptor also in the adrenocortical cells, thereby modulating its own synthesis. Design and method: APA strips and adrenocortical carcinoma cell line HAC15 were exposed to [100 nM] aldosterone for 12 hours in the presence or absence of the selective mineralocorticoid receptor (MR) antagonist canrenone and/or of the selective GPER-1 antagonist G36. HAC15 cells were silenced for GPER-1 with specific small interfering RNA (siRNA) and then exposed to aldosterone. The changes of aldosterone synthase (CYP11B2) mRNA and protein levels were measured by real time qRT-PCR and immunoblotting. Results: Aldosterone increased CYP11B2 gene and protein expression (+200% and +130%, respectively) in HAC15 cells (p < 0.001 vs untreated). Pretreatment with canrenone did not prevent such increase, while G36 abolished aldosterone-induced CYP11B2 activation (p < 0.01). In APA strips aldosterone increased CYP11B2 gene expression (+330%, p < 0.01 vs untreated); pre-treatment with G36 blunted this effect of aldosterone. Silencing of GPER-1 with siRNA not only reduced GPER-1 expression (p < 0.01), but also abolished the CYP11B2 increase in response to aldosterone. Conclusions: Aldosterone enhances the expression of CYP11B2 acting via GPER-1, but not MR. Binding of aldosterone to GPER-1 could contribute to perpetuating the autonomous aldosterone excess, which is a hallmark of primary aldosteronism, via an autocrine-paracrine positive feed-back loop.